2014
DOI: 10.1055/s-0034-1372587
|View full text |Cite
|
Sign up to set email alerts
|

Laryngomalacia and Complicated, Life-threatening mTOR-positive Kaposiform Hemangioendothelioma Cured by Supraglottoplasty and Sirolimus

Abstract: The therapy of complicated Kaposiform hemangioendothelioma (KHE) is still difficult. We present the first case of laryngomalacia with simultaneous mammalian target of Rapamycin (mTOR)-positive KHE of the neck and thoracic inlet and concurrent Kasabach-Meritt Phenomenon (KMP) in an 11-month-old boy suffering life-threatening progress despite intravenous vincristine, corticosteroids, propranolol and local interstitial laser-application. The laryngomalacia restored after laser-supraglottoplasty. Successfully trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Sirolimus was chosen as a treatment option, given a growing body of work investigating its role in the management of complicated vascular tumors . Our patient's contracture and disability were felt to be secondary to the infiltrative nature of his tumor involving the soft tissue of his right thigh, but also the accompanying fibrosis that complicates KHE over time.…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus was chosen as a treatment option, given a growing body of work investigating its role in the management of complicated vascular tumors . Our patient's contracture and disability were felt to be secondary to the infiltrative nature of his tumor involving the soft tissue of his right thigh, but also the accompanying fibrosis that complicates KHE over time.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, sporadic reports on the use of sirolimus in the management of KHE, a vascular tumor of borderline malignancy, confirm its effectiveness in this entity [2,10,14,23]. In 2011, Hammill et al reported on five patients with complicated lymphatic malformations and one patient with KHE who were treated with sirolimus after failing multiple other therapies [10].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Hammill et al reported on five patients with complicated lymphatic malformations and one patient with KHE who were treated with sirolimus after failing multiple other therapies [10]. There are only sporadic further case reports on the use of sirolimus in children with different vascular anomalies, namely KHE and/or lymphatic malformations [13,15,23,28]. In accordance to these data, two patients with KHE and KMP in our series (patients 3 and 6) improved dramatically under sirolimus without experiencing any significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…Review of available literature does not support an increased risk of bleeding with use of antiplatelet agents in KMS, especially when there is no active bleeding. Although the data is controversial, the combination of aspirin and Ticlopidine appears to be the safest and most effective option [76][77][78][79][80]. Enjolras et al reported that this combination was effective in 32% of patients in one series and 29% in another series [63,81,82].…”
Section: Antiplatelet Therapymentioning
confidence: 99%